(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Sports entrepreneurship among countries is to achieve a good sporting performance in sportive competitions.At the present time, sports are considered as one of the essential parts in our life, which are sought out bythe governments, due to the main role that sports take at the national and international levels in the political,economic, cultural and social levels.The sports level has been improving over the past several decades, this improving coinciding with thechanges of the sport concept that is generally recognised as system of activities which are based in physicalathleticism or physical dexterity. The concept of the athlete has changed into a wide concept that is becomea unit of feeling, excited, affected and tired.Sports has got the attention of persons who interested in scientific, medical, social, political and economicmatters, which made sports have different specializations such as administration and management.